Implicatures Used as a Means to Develop the Plot in the Soundtracks of Encanto Movie - Hadisusilo, Keiza Gunawan; Murniati, Cecilia Titiek; Diasti, Krismalita Sekar (Celt: A Journal of Culture, English Language Teaching & Literature, 2023)
This paper analyzes the usage of implicatures in soundtracks for plot developments in Disney’s 2021 movie Encanto. An implicature, at its core, functions as a means to provide context or a deeper level of understanding that is otherwise invisible unless the listener understands the topic at hand. Such is why the usage of implicatures can be seen as literary devices, either in song lyrics or movie scripts. By comprising evidence from diaries on this topic and research conducted on this study, this paper outlines implicatures present in songs being used as a means of plot development for the movie in which the song originates. This study found that by using the concept of Gricean Maxim's flouting, a theory proposed in the study of implicatures, lyrics of soundtracks containing implicatures can be used as a means of establishing a status quo, foreshadowing future events that may later happen in the movie as either a comedic effect or alluding to real life situations for poetic effect, and also by presenting it in a more word-structurally format.